An ecological risk assessment for the impacts of offshore wind farms on birds in Australia. (12th January 2023) - Reid, Keith; Baker, G. Barry; Woehler, Eric J.
Abstract: An ecological risk assessment, based on life‐history and behavioural attributes of 273 bird taxa, was used to identify which of those taxa are at high risk from negative interactions with offshore wind farms in Australia. The marine area of Australia was divided by state/territory boundaries perpendicular to the coast into eight regions, with Western Australia further divided into north and south, and a Bass Strait region bounded by the Victoria coast and the north coast of Tasmania. These regions were subdivided into coastal, inshore and offshore sub‐regions and a risk summary for all bird taxa occurring in each of these sub‐regions produced. In coastal and inshore sub‐regions of Bass Strait, South Australia and Tasmania, the species with the highest risk scores were Orange‐bellied Parrot Neophema chrysogaster, Furneaux White‐fronted Tern Sterna striata incerta, Swift Parrot Lathamus discolor, Shy Albatross Thalassarche cauta, Far Eastern Curlew Numenius madagascariensis and Anadyr Bar‐tailed Godwit Limosa lapponica anadyrensis . In offshore sub‐regions in southern Australia, the highest risk species were all albatrosses, comprising Northern Royal Diomedea sanfordi, Eastern Antipodean D. antipodensis antipodensis, Gibson's D. antipodensis gibsoni, Wandering D. exulans, Amsterdam D. amsterdamensis and Grey‐headed Albatross T. chrysostoma . Compared to onshore installations, there are logistical challenges to quantifying the potential and realized impacts of offshore wind farms that require different approaches to data collection and analyses. The extensive development of offshore wind farms in the Northern Hemisphere provides examples of best and emerging approaches to quantify and mitigate negative impacts of offshore wind farms that can be applied in an Australian context. Despite differences in the species involved, the same approaches to identifying high‐risk species and to the monitoring and mitigation of negative impacts should be applied in a coordinated, regional‐scale approach to the development of offshore wind farms in Australia.